Kajian Pertumbuhan dan Produksi Tomat (Solanum licopersicum Mill) Terhadap Zat Pengatur Tumbuh Pada Macam Konsentrasi dan Waktu Pemberian. - Amiroh, Ana (Universitas Islam Darul Ulum, 2016)
The purpose of this study to determine the Productivity Assessment Tomato (Solanum licopersicum Mill) were treated with plant growth regulators on the concentration and a different timing. The research was carried on in the village Tawangrejo, sub Turi, Lamongan district, with a height of Â± 5 m above sea level. This study uses a randomized block design (RAK) factorial consisting of 2 factors and 3 replications. The first factor is timing of plant growth regulator with 3 levels, among other things W1 = Morning (09.00); W2 = Lunch (12.00); W3 = afternoon (15:00). The second factor is concentration of PGR administration with 3 levels are: D1 = 2cc / lt of water, D2 = 4cc / lt of water, D3 = 6cc / lt of water. There is no interaction time of administration and concentration of plant growth regulators at the variable plant height 14, 21, and 28 days after planting, stem diameter at 21 and 28 days after planting, the number of leaves at 28 days after planting, fruit weight per sample, weight of the fruit per plot, the average weight per fruit at harvest first, second, and third. There is a real difference between the time of administration and concentration of plant growth regulators at the variable stem diameter at 28 days after planting, the number of leaves at 14 days after planting, fruit weight per sample of the first harvest, and the third, by weight of fruit per plot on the third harvest, the average weight -rata apiece in the third harvest. The results of the best research on the combination of the timing of the morning with a concentration Award 6cc / l water plant growth regulator.